2010
DOI: 10.4103/0019-557x.75734
|View full text |Cite
|
Sign up to set email alerts
|

Hand washing practices in two communities of two states of Eastern India: An intervention study

Abstract: Based on the findings of the study, it could be suggested that Behaviour Change Communication program should be further planned with emphasis on different components of hand washing with a final objective to bring down the incidence of target diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
4
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
4
16
4
3
Order By: Relevance
“…This differs from the study by Ray SK in two communities of eastern India where hand washing was not practiced before "preparing food" and after handling raw vegetables [19]. In a study conducted at coastal Karnataka India, majority of the mothers wash their hands with soap and water after defecation (90%) and after cleaning child's bottom (87.8%) but fewer women wash their hands before cooking (31.1%), before eating (33.3%) and before feeding the child (38.9%) [19]. It was observed in the present study that majority (4/5th) of the study population used soap & water for washing hands.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This differs from the study by Ray SK in two communities of eastern India where hand washing was not practiced before "preparing food" and after handling raw vegetables [19]. In a study conducted at coastal Karnataka India, majority of the mothers wash their hands with soap and water after defecation (90%) and after cleaning child's bottom (87.8%) but fewer women wash their hands before cooking (31.1%), before eating (33.3%) and before feeding the child (38.9%) [19]. It was observed in the present study that majority (4/5th) of the study population used soap & water for washing hands.…”
Section: Discussioncontrasting
confidence: 75%
“…Praveen N et all in their study explored that, hand washing before preparing food & before serving food is being practiced by 76.8% & 57.4% of mothers [11]. This differs from the study by Ray SK in two communities of eastern India where hand washing was not practiced before "preparing food" and after handling raw vegetables [19]. In a study conducted at coastal Karnataka India, majority of the mothers wash their hands with soap and water after defecation (90%) and after cleaning child's bottom (87.8%) but fewer women wash their hands before cooking (31.1%), before eating (33.3%) and before feeding the child (38.9%) [19].…”
Section: Discussionmentioning
confidence: 98%
“…Handwashing frequency before the meals (61 %) found in our study is similar to results of some studies (for instance 53 % in China and 73 % in Korea) and the handwashing frequency before cooking (68 %) found in our study is higher than some of other studies (for instance 35 % in Bangladesh and 42 % in Kenya) [17,[31][32][33]. The handwashing frequency after the toilet in our study (91 %) is higher than most of similar studies.…”
Section: Discussionsupporting
confidence: 93%
“…[12] Around three-fourth did not store water in a proper way in a utensil, and nearly half of them use un-cleaned utensils similar to Reddy et al [2] Open defecation was still a reported practice in the study area and 29% women reported about open defecation similar to study of Kuberan et al [12] and lower than data of NFHS 4, Uttar Pradesh [11] and Reddy et al [2] In this study only one-third of women washed their hands before eating and food preparation and merely 38% using soap for hand washing after defecation. Our finding was lower as compared to the study of Reddy et al, [2] Ray et al, [13] and Wilson. [14] The study shows significant association with hand washing habits and place of defecation.…”
Section: Discussioncontrasting
confidence: 56%